2001
DOI: 10.1016/s1074-7613(01)00101-7
|View full text |Cite
|
Sign up to set email alerts
|

STAT-3 Activation Is Required for Normal G-CSF-Dependent Proliferation and Granulocytic Differentiation

Abstract: To investigate the role of signal transducer and activator of transcription (STAT) proteins in granulocyte colony-stimulating factor (G-CSF)-regulated biological responses, we generated transgenic mice with a targeted mutation of their G-CSF receptor (termed d715F) that abolishes G-CSF-dependent STAT-3 activation and attenuates STAT-5 activation. Homozygous mutant mice are severely neutropenic with an accumulation of immature myeloid precursors in their bone marrow. G-CSF-induced proliferation and granulocytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
155
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(172 citation statements)
references
References 47 publications
15
155
1
1
Order By: Relevance
“…This result suggests a direct effect of IFN␥ in activating this signaling pathway that, in several in vitro studies, is shown to link cytokine signaling with cell proliferation. 30,31 Collectively, these data provide compelling evidence that IFN␥ signaling is required for an optimal oval cell response.…”
Section: Discussionmentioning
confidence: 95%
“…This result suggests a direct effect of IFN␥ in activating this signaling pathway that, in several in vitro studies, is shown to link cytokine signaling with cell proliferation. 30,31 Collectively, these data provide compelling evidence that IFN␥ signaling is required for an optimal oval cell response.…”
Section: Discussionmentioning
confidence: 95%
“…Although STAT3 has been linked to myeloid cell differentiation (17,51), STAT5 seems to be involved in G-CSF-dependent cell proliferation (18). Because we found a potent induction of SOCS-3 mRNA in U937 cells as well as in primary neutrophils upon G-CSF stimulation, we examined the impact of SOCS-3 on G-CSF-induced STAT DNA binding by means of a STAT-luciferase assay.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Stat3C expression did not abrogate growth factor dependence and had no effect on IL-3-dependent growth, similar to what was previously reported for bone marrow cells. 25 A 'stabilized' PI3-kinase expressed in DKI cells is substantially able to restore CSF-1-dependent mitogenesis…”
Section: Csf-1-dependent Mitogenesis Requires Both Erk and Pi3-kinasementioning
confidence: 99%